CANT EXCESS AND CANT DEFICIENCY EVALUATION IN RELATION TO TRAIN SPEED - Valehrach, Jan; Říha, Tomáš; Říha, Tomáš; Dušek, Erik (České vysoké učení technické v Praze, 2017)
The paper deals with the evaluation of measured speeds of the vehicles on the chosen sections of the railway network in the Czech Republic. In connection with the phased implementation of the AVV system (automatic train operation) and the European ETCS system, the dispersion of the train speeds will be reduced. Measured data were used to assess the weighted average of the cant excess or cant deficiency in relation to the rail defects. Within the framework of the research, the speeds were statistically evaluated covering more aspects like types and sorts of the trains, their operators, daytime and more.